Need for orthodontic treatment among children in Foča - Predrag Nikolić; Ljiljana Stojanović; Tanja Ivanović; Dragan Ivanović; Marina Milinković; Bojan Joksimović (Биомедицинска истраживања, 2017)
Introduction: Orthodontic treatment is a common dental procedure in developedcountries. Assessment of orthodontic treatment need is importantfor health services planning and population trends monitoring. The aim ofthis study was to assess the need for orthodontic treatment among childrenin Foča, Bosnia and Herzegovina. Methods: The study involved 81 students of two primary schools in themunicipality of Foča, aged 11-13 years. The subjects underwent clinicalexaminations, the dental impressions were taken, study models were madeand analyzed, and digital photographs of anterior dentition were taken too.Index of Complexity, Outcome and Need (ICON) was used to assess theneed for orthodontic treatment. The number of orthodontists, which wouldbe sufficient to meet the needs of this population of children, was estimated. Results: ICON index results showed that 56.8% of children needed orthodontictreatment. There was no statistical significance in the need for orthodontictreatment between the subjects of different gender and age. The study showedthat 22.2% of boys and 34.6% of girls needed orthodontic treatment. In relationto age, 21% of eleven- and 21% of twelve-year-olds needed orthodontictreatment and 14.8% of thirteen-year-olds. The incidence of crowding was80.2%. Crossbite was present in 23.5% of examined students, open bite in 2.5%,deep bite in 29.6% and irregular dental esthetics anterior teeth in 28.4%. ClassII/1 malocclusion was found in 39.5% of children, II/2 class in 9.9%, class I in38.3%, while class III malocclusion was found in 9.9% of examined children. Conclusion: The study shows that a large percentage of children in Foča needorthodontic treatment. Percentage of the need for orthodontic treatment ishigher in comparison to most of the countries in Europe and the world. Thedevelopment of prevention programs and early caries therapy can greatlyreduce the need for orthodontic treatment.
Keywords: orthodontics; orthodontic treatment; ICON index; treatment need indices